Acknowledgment and avoidance in Coleridge and Hölderlin - Wayne Deakin (2018)
© 2015 Taylor and Francis. In this paper I propose a reading of Coleridge and Hölderlin using Stanley Cavells philosophical theory of acknowledgment and avoidance as an interpretive rubric. I argue that recognition (acknowledgment) of the skeptical limits of reason and the imagination allow Hölderlin, through his poetical theory, philosophy and practice, to overcome the epistemological limits of the romantic imagination; this factor is instanced in his poetry. On the other hand, Coleridge's work remains trapped within skeptical limits because of his "avoidance" of this ontological recognition, which is due to his continued desire for an intellectual intuition. I further my argument by using the hermeneutics of Heidegger as a secondary tool in reading both poets and in helping to illuminate their relative poetic and philosophical positions. Both poets ultimately recognize the limits of our imaginative autonomy; however, they articulate these limits in very different ways-ways that are useful keys in unlocking the work of Coleridge and Hölderlin.